Contribution to the study of the impact of Covid 19 on the management of accounting results : Case of the Telecommunications and New Technologies Sector in Morocco. - NEJJAR , WAFAE NADA; BENTHAMI , ZINEB (Revue du contrôle, de la comptabilité et de l’audit, 2022)
The impact of the current epidemic on the management of accounting results is still an open research topic. This article focuses on the management of corporate accounting results in the first year of the pandemic. The theoretical framework is based on political-contractual theory, agency and regulatory theory, and governance and accounting threshold theory. Our study differs from existing studies in that it focuses on a sector that has been able to continue its activity despite the crisis situation. At the end of the analysis, annual financial reports published on the website of the Moroccan Capital Market Authority were used in the empirical part to verify ex-post whether earnings management has taken place for all listed companies in the telecommunications and new technologies sector. Our results were used to verify the hypotheses relating to errors on the Eviews software using the Panel model. The result obtained confirms the existence of such an operation. As a perspective to this work, we propose further research that addresses the influence of the factors and reasons that may push the managers of these companies to such legal manipulations in a crisis context such as the COVID-19 period.